The Effectiveness of Physical and Chemical Defense Responses of Wild Emmer Wheat Against Aphids Depends on Leaf Position and Genotype - Singh, Anuradha; Dilkes, Brian; Sela, Hanan; Tzin, Vered (Frontiers in Plant Science, 2021)
The bird cherry-oat aphid (Rhopalosiphum padi) is one of the most destructive insect pests in wheat production. To reduce aphid damage, wheat plants have evolved various chemical and physical defense mechanisms. Although these mechanisms have been frequently reported, much less is known about their effectiveness. The tetraploid wild emmer wheat (WEW; Triticum turgidum ssp. dicoccoides), one of the progenitors of domesticated wheat, possesses untapped resources from its numerous desirable traits, including insect resistance. The goal of this research was to determine the effectiveness of trichomes (physical defense) and benzoxazinoids (BXDs; chemical defense) in aphid resistance by exploiting the natural diversity of WEW. We integrated a large dataset composed of trichome density and BXD abundance across wheat genotypes, different leaf positions, conditions (constitutive and aphid-induced), and tissues (whole leaf and phloem sap). First, we evaluated aphid reproduction on 203 wheat accessions and found large variation in this trait. Then, we chose eight WEW genotypes and one domesticated durum wheat cultivar for detailed quantification of the defense mechanisms across three leaves. We discovered that these defense mechanisms are influenced by both leaf position and genotype, where aphid reproduction was the highest on leaf-1 (the oldest), and trichome density was the lowest. We compared the changes in trichome density and BXD levels upon aphid infestation and found only minor changes relative to untreated plants. This suggests that the defense mechanisms in the whole leaf are primarily anticipatory and unlikely to contribute to aphid-induced defense. Next, we quantified BXD levels in the phloem sap and detected a significant induction of two compounds upon aphid infestation. Moreover, evaluating aphid feeding patterns showed that aphids prefer to feed on the oldest leaf. These findings revealed the dynamic response at the whole leaf and phloem levels that altered aphid feeding and reproduction. Overall, they suggested that trichomes and the BXD 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one (DIMBOA) levels are the main factors determining aphid resistance, while trichomes are more effective than BXDs. Accessions from the WEW germplasm, rich with trichomes and BXDs, can be used as new genetic sources to improve the resistance of elite wheat cultivars.